The psychological effects of the media - Social media - on adolescent behavior- a field study on a sample of adolescents in hammadi krouma high school- skikda- - Kheribeche, Kheribeche; Yahi, Abdelmalek (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study seeks to address: the psychological effects of social media communication on adolescents behavior. As one of the most critical topics of interest to various researchers specializing in the social and educational sciences We have clarified the general theoritical, view of the study by presenting the research problem and its hypotheses, defining the study concepts , objectives ,and importance, and presenting some previuos studies. The understand the reality of the phenomenon studied in the field,we followed an integrated methodology, that was clear in our reliance on the descriptive approach. We chose a research sample that included 26 respondents. We also relied on tools to collect field information, especially the questionnaire and the interview, to provide more realistic topic indicators. Based on field data and analytical readings, the most important of which is that social media has significant psychological effect on adolescents behavior, especially those related to the behavioral and sexual aspects. It remains only to point out. Finally, Increasing or decreasing the level of these effects is related to the extent, of the nature of the means of communication used by the teenager.